Nanopartículas no tratamento e controle de fungos fitopatogênicos em sementes de soja armazenadas - Pontes, Brenda Santos (2025)
The nanoparticles (NPs) exhibit promising physicochemical properties for antimicrobial control. It is essential that they are biocompatible and specific, avoiding issues such as phytotoxicity and the selection of resistant microorganisms. In soybean cultivation, seed treatment with NPs can offer an efficient and environmentally responsible approach for controlling phytopathogenic fungi, protecting the seeds and preserving their longevity. This study aimed to characterize nanoparticles and evaluate the effectiveness of soybean seed treatment, considering both the preservation of seed quality and the control of phytopathogenic fungi during storage. The experiment was conducted in a completely randomized design, with treatments arranged in a 6 × 4 factorial scheme, consisting of six seed treatments [ZnO:Mo; ZnO:K; ZnO; ZnO:Mg; Fungicide (Thiophanate-methyl + Fluazinam); Control (water)] and four storage periods (0, 45, 90, and 135 days), with four replicates. Nanoparticle characterization was performed using scanning electron microscopy (SEM), X-ray diffraction (XRD), and transmission electron microscopy (TEM). For the assessment of physical and physiological seed quality, the following variables were analyzed: moisture content, germination convencional and with vermiculite, seedling length, growth index, uniformity index, vigor index, emergence, mean emergence time (MET), accelerated aging conventional and with vermiculite. For the evaluation of sanitary quality, the Blotter Test was conducted. The nanoparticles exhibited a polycrystalline wurtzite structure, and microscopic images revealed rod-shaped particles adhered to the soybean seed coat, with the presence of zinc and oxygen. The effect of nanoparticle treatments on soybean seed quality exhibited variable behavior depending on the storage period, with observed effects ranging from phytotoxicity to improvements in physiological performance. The nanoparticles demonstrated potential and were effective in controlling phytopathogenic fungi in soybean seeds during the storage period.